ARTISTIC GYMNASTICS IN HIGHER EDUCATION: IMPLEMENTATION OF SPORT EDUCATION FROM THE FREIRIAN PERSPECTIVE - Lopes, Priscila (2023)
The objective of the research was to understand the pedagogical strategies mediated by a teacher educator in an undergraduate course in Physical Education in the implementation of Sport Education (SE) to develop knowledge about Artistic Gymnastics (AG) based on the Freirean pedagogy. Action research was used as a research method, with the implementation of the pedagogical process developed over 12 weeks with the participation of the teacher educator and 17 students. Data were collected weekly and included: pedagogical documentation produced during the course; field diaries written by the teacher educator at the end of each meeting; discussions with a critical friend during the development of the educational process; and focus groups after the entire process. Thematic Analysis was used to analyze the data. The results indicate that the three pedagogical strategies were fundamental for the implementation of SE in GA: Experience of different roles, Dynamics of design and Co-creation of the AG code. This set of strategies characterizes a pedagogical mediation consistent with Paulo Freire's pedagogical proposal by highlighting fundamental knowledge inherent to the ethical nature of a liberating educational practice, namely: Reading the world, Investigative spirit, Stimulating autonomy, Horizontality, Problematization and (Re)construction of (new) knowledge.